DEVELOPMENT OF “My Home” MODULE BASED ON GRESIK LOCAL WISDOM FOR ELEMENTARY SCHOOL - Yani, Widi; Setya Nugroho, Arya; Khoirul Umam, Nanang (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This research is motivated by teachers who still rarely use the companion module, especially on the material of geographical conditions. So this study aims to determine the validity and effectiveness of the learning module "My Home" for Class IV MI. Al-Mathlabatul Khoiriyah. The method in this study uses a 4-D model but the researcher only uses 3 stages, namely, define, design, develop. In the development stage, researchers validate, revise, and test 10 students. So that the data collection techniques used are validation of linguists, materials, graphics, culture, and the distribution of response questionnaires. The subjects in this study were 4 expert validators. The results of the development of this learning module meet the feasibility indicators of the expert validators. The results of the validation of linguists got a score of 82.5%, material, and graphic experts got a score of 81.5%, cultural experts got a score of 96%, and includes very decent criteria. The novelty of this research lies in the illustration of the design of the learning modules used, and the subject matter related to the culture in Gresik. Based on the validation results, this learning module can be used in the learning process.